Attributes of effective collaboration: insights from five case studies in Australia and New Zealand - Butcher, John; Gilchrist, David J; Phillimore, John; Wanna, John (Taylor & Francis Onlie, 2019)
Developing and implementing social policy aimed at resolving wicked problems has occupied governments and not-for-profit organizations for decades. Such problems are enduring due to their complexity, resulting in a need to harness multiple skills and significant resources to the effort to solve them. Collaboration is one response to this need and is logical because such arrangements have the potential to bring to bear differing experiences, greater resources, and a higher level of understanding. However, collaboration is not easy and, if not done well, can result in significant costs in time and money as well as poor outcomes for those affected. In this paper, we identify the necessary attributes of successful collaborations by examining five case studies that provide important insights into sound collaborative practice.